The German-Jewish Experience Revisited - Aschheim, Steven E.; Liska, Vivian (Perspectives on Jewish Texts and Contexts, 2015)
This volume includes both historical treatments of differing German-Jewish understandings of their experience &#8211 their relations to their Judaism, general culture and to other Jews &#8211 and contemporary reflections and competing interpretations as to how to understand the overall experience of German Jewry.